Knowledge-Sharing Enablers and Barriers in Research Centers: A Literature Review - Rohman, Abdul; Eliyana, Anis; Purwana, Dedi (KnE Social Sciences, 2020)
The purpose of the study is to explore the enablers and barriers of knowledge-sharing and consider how knowledge-sharing is implemented by research centers. The literature review covers journals which are indexed (Scopus, ProQuest, and Thomson Reuters) and specialized in knowledge-sharing in research centers. The papers could be easily explored using the key search terms via search engines such as Google Scholar, Emerald Insight, and ProQuest. The review process included the studies from 1994 to 2018. Key search terms include “knowledge management”, “knowledge sharing”, “knowledge sharing enablers and barriers”, and “research centers” to reduce interpretation bias. Individual enabler factors supporting knowledge-sharing consist of social relations and networks, physical proximity to colleagues, a ‘no stupid questions’ culture, monetary rewards, trust, openness in communication, interactive communication, and intrinsic motivational factors. Meanwhile organisational factors include the provision of meeting facilities and informal spaces, appreciation of research by firms and society, diffusion and routine dissemination, simplification of the patenting process, organizational rewards, organizational culture, intention to knowledge sharing methods, extrinsic motivation factors, and others (teamwork, and solid research team). The study was approached from a theoretical perspective and the model proposed can be empirically validated by identifying statements for each dimension. Future research should explore more empirical studies from different countries especially case studies in research centers. Keywords: knowledge management, knowledge sharing enablers and barriers, research centers